The effect of clearance control on the performance of an oil-free linear refrigeration compressor and a comparison between using a bleed flow and a DC current bias - Liang, K; Dadd, M; Stone, R; Bailey, P (Elsevier, 2016)
A moving magnet type oil-free linear compressor has been designed for applications such as electronics cooling. A control system using a solenoid operated valve was developed for DC offset and axial clearance control. Operation of the linear compressor with a fixed clearance of 0.8 mm was compared with a zero DC offset operation. The fixed clearance operation requires a higher power input. The mean piston position can be controlled by using a DC bias on the drive voltage or by using a bleed flow from the compressor body to the suction side of the compressor. Using a DC bias on the drive voltage induces a higher power loss than using a bleed flow when there is a small radial clearance between the piston and cylinder. This provides evidence that the piston control in a refrigeration system with capacity control should be for a zero DC offset using a bleed flow.